Relationship between mediterranean diet, physical activity and body mass index in adolescent of high school of two villages in Granada - Peláez-Barrios, E. M.; Vernetta-Santana, M.; López-Bedoya, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The objetive was evaluate the Adherence to Mediterranean Diet (AMD) in adolescents and the relationship with the Body Mass Index (BMI) and Physical Activity (PA). he study was realized with 209 adolescents (117 girls y 92 boys), between 12 and 18 years. he AMD was analysed through the KIDMED test and PA level was estimated using the International Physical Activity Questionnaire (IPAQ short version. he height and weigth was measured of each gymnastics, calculating BMI. he 65,6%, of the total sample showed an optimal AMD with a BMI of 20.02 kg/m2 without sex diferences. However, the boys showed signiicantly bigger physical activity level than girls. No signiicant relationships were found between variables MD, PA, BMI and gender. he habits of the Spanish adolescents in the sample are healthy, presenting the most optimal AMD, normal values of BMI and in good level of PA.